2004
DOI: 10.5863/1551-6776-9.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentrations Following Application of Whole versus Cut Transdermal Clonidine Patches To Critically Ill Children

Abstract: Clonidine is used for hypertension and narcotic withdrawal prophylaxis in adults and children. This study described plasma absorption of clonidine from whole and cut transdermal clonidine patches. This was a retrospective descriptive study in an 18 bed multidisciplinary pediatric intensive care unit, evaluating 15 critically ill children with a median age of 1.1 years (range 0.3-11 years) treated with transdermal clonidine for narcotic withdrawal prophylaxis, and who had plasma clonidine concentrations measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Based on a review of the published data, clonidine may provide beneficial effects as an adjunct therapy for sedation and analgesia and drug withdrawal. Thirty‐one patients (27.1%) included in this review received clonidine as part of a pharmacokinetic study that did not focus on clinical outcomes . Fifty (43.9%) received clonidine for sedation and analgesia while mechanically ventilated .…”
Section: Practical Applicationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on a review of the published data, clonidine may provide beneficial effects as an adjunct therapy for sedation and analgesia and drug withdrawal. Thirty‐one patients (27.1%) included in this review received clonidine as part of a pharmacokinetic study that did not focus on clinical outcomes . Fifty (43.9%) received clonidine for sedation and analgesia while mechanically ventilated .…”
Section: Practical Applicationsmentioning
confidence: 99%
“…Some reports have described utilizing transparent film dressing to occlude part of the patch or cutting the patch into quarters (e.g., 0.025 mg/day) or halves (e.g., 0.05 mg/day). These practices should be discouraged because it was reported that the patients receiving cut patches had significantly higher concentrations of clonidine than those with whole patches. No pharmacokinetic data have evaluated occlusion of a clonidine patch with transparent film dressings.…”
Section: Practical Applicationsmentioning
confidence: 99%
See 3 more Smart Citations